Sjogren's syndrome: autoimmune epithelitis - Moutsopoulos, Haralampos (Henry Stewart Talks, 2007)
Characteristics and clinical symptoms of Sjogren's syndrome (SS), The epithelial component is the mainly affected tissue; injury is associated with dense lymphocytic infiltrates by activated T and B cells, The epithelial cell is a pivotal regulator of the SS autoimmune responses, SS is actually an autoimmune epithelitis, Non-neoplastic salivary gland epithelial cell (SGEC) lines, Epithelial cells possibly participate in the perpetuation of inflammatory responses and to the introduction of autoantigens in the immune system, The critical role of epithelial cells in the regulation of local immune responses in salivary glands
Archived at 2021/02/25